Analysis and prospects for blockchain testing and evaluation - Peiyu Zheng; Mengwei Han; Haiyan Kuang; Heng Yuan; Xiaofeng Chen (Blockchain)
With the strong support of various countries’ policies, blockchain technology is booming in all walks of life, and the demand for blockchain evaluation is also growing. Relevant authoritative organizations have begun to formulate blockchain evaluation standards and carry out evaluations on the blockchain platforms and application products, providing reliable information for the government, industry authorities, blockchain users and investors in the blockchain selection stage. This article introduces mainstream blockchain evaluation institutions, analyzes the status of blockchain evaluation standards, sorts out blockchain evaluation tools and methods, and summarizes the current development of the blockchain evaluation industry based on the relevant status quo. This article also gives some suggestions for future development in terms of improving the implementation of blockchain evaluation standards, improving blockchain evaluation tools, formulating international standards for blockchain evaluation, and strengthening the training of blockchain evaluation talents.